Efektivitas Model Pembelajaran Diskusi Kelas Strategi Beach Ball Terhadap Hasil Belajar IPA Peserta Didik - Aloysius Djalo; Hildegardis Missa; Sardina Ndukang; Anselmuas Boy Baunsele (Jurnal PTK dan Pendidikan, 2023)
Abstract: The cause of the low student learning outcomes is the learning process in the classroom which is still teacher-centered. The learning model that can increase student activity in class is the Beach Ball strategy class discussion model. The purpose of this study was to determine the effectiveness of the Beach Ball strategy class discussion model on science learning outcomes for Grade VIII students on the subject of the human digestive system at SMPN 2 Kupang Tengah. The design used in this research is nonequivalent control group design. The results showed that the average student learning outcomes in the experimental class obtained a pretest score of 41.86 which increased to 80.31 after being given a posttest. Whereas in the control class the pretest score was 45.47 which increased to 74.11 after being given the posttest. Based on the results of the one-way Anacova test, a probability value (sig) of 0.000 is lower than the set value of 0.05. This shows that Ha (Beach Ball strategy class discussion model is effective on student learning outcomes) is accepted and H0 the Beach Ball strategy class discussion model is not effective on student learning outcomes) is rejected. Based on the results of data analysis, it can be concluded that the Beach Ball strategy class discussion model is effective on the learning outcomes of class VIII students at SMPN 2 Kupang Tengah.Keywords:  Effectiveness, Class Discussion, Beach Ball, Learning Outcomes, Food DigestionAbstrak: Penyebab rendahnya hasil belajar siswa adalah proses pembelajaran di kelas yang masih berpusat pada guru. Model pembelajaran yang mampu meningkatkan keaktifan siswa di kelas adalah model diskusi kelas strategi Beach Ball. Tujuan penelitian ini adalah untuk mengetahui efektifitas model diskusi kelas strategi Beach Ball terhadap hasil belajar IPA siswa kelas VIII pada materi sistem pencernaan makanan pada manusia di SMPN 2 Kupang Tengah.  Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan metode Eksperimen Semu. Desain yang digunakan dalam penelitian ini adalah nonequivalent control group design. Hasil penelitian menunjukkan bahwa rata-rata hasil belajar siswa pada kelas eksperimen memperoleh nilai pretest sebesar 41,86 meningkat menjadi 80,31 setelah diberikan posttest. Sedangkan pada kelas kontrol nilai pretest adalah 45,47 meningkat menjadi 74,11 setelah diberikan posttest. Berdasarkan hasil uji anacova satu jalur diperoleh nilai probabilitas (sig) sebesar 0,000 lebih kecil dari nilai yang ditetapkan sebesar 0,05. Hal ini menunjukkan bahwa Ha (model diskusi kelas strategi Beach Ball efektif terhadap hasil belajar siswa) diterima dan H0 model diskusi kelas strategi Beach Ball tidak efektif terhadap hasil belajar siswa)ditolak. Berdasarkan hasil analisis data dapat disimpulkan bahwa model diskusi kelas strategi Beach Ball efektif terhadap hasil belajar siswa kelas VIII di SMPN 2 Kupang Tengah. Kata Kunci: Efektif, Diskusi Kelas, Beach Ball, Hasil Belajar, Pencernaan Makanan